"Kans Is King and the Cultivator Is His Subject": Environmental History and Agrarian Development in Modern India. Issue 1 (14th December 2020) - Siegel, Benjamin
Abstract: Throughout the nineteenth and twentieth centuries, cultivators and administrators in India contended with the ravages of kans grass ( Saccharum spontaneum ), a deeply rooted wild sugarcane capable of rendering productive land wholly barren. Difficult to eliminate and endemic throughout India, kans disrupted agricultural efforts in north and central India, particularly in the regions of Jhansi, Bundelkhand, and the Himalayan Terai. Yet the fight against this ecological antagonist was bound up in broader political transformations. As India's colonial agriculture grew increasingly tied to global markets in the late nineteenth century, and dry regions offered new possible spaces for settled agriculture, imperial administrators grew certain that mechanical tractors held the solution to its eradication. Likewise, postcolonial Indian agronomists cast the production of abundant food as central to their political legitimacy, and they made the eradication of kans a national aim, enlisting the World Bank as a partner. British administrators, nationalist Indians and their postcolonial successors, as well as the World Bank all found a mechanized approach to the eradication of kans politically expedient, at the expense of heeding local ecological and social conditions . The remarkable resilience of kans defied efforts at mechanical removal, and the project foundered until the political economy of Indian agriculture shifted to emphasize chemical pesticides and decentralized control.